Risk Factors for Prolonged Opioid Use Following Spine Surgery, and the Association with Surgical Intensity, Among Opioid-Naive Patients. (2nd August 2017) - Schoenfeld, Andrew J.; Nwosu, Kenneth; Jiang, Wei; Yau, Allan L.; Chaudhary, Muhammad Ali; Scully, Rebecca E.; Koehlmoos, Tracey; Kang, James D.; Haider, Adil H.
Abstract : Background: There is a growing concern that the use of prescription opioids following surgical interventions, including spine surgery, may predispose patients to chronic opioid use and abuse. We sought to estimate the proportion of patients using opioids up to 1 year after discharge following common spinal surgical procedures and to identify factors associated with sustained opioid use. Methods: This study utilized 2006 to 2014 data from TRICARE insurance claims obtained from the Military Health System Data Repository. Adults who underwent 1 of 4 common spinal surgical procedures (discectomy, decompression, lumbar posterolateral arthrodesis, or lumbar interbody arthrodesis) were identified. Patients with a history of opioid use in the 6 months preceding surgery were excluded. Posterolateral arthrodesis and interbody arthrodesis were considered procedures of high intensity, and discectomy and decompression, low intensity. Covariates included demographic factors, preoperative diagnoses, comorbidities, postoperative complications, and mental health disorders. Risk-adjusted Cox proportional hazard models were used to evaluate the time to opioid discontinuation. Results: This study included 9, 991 patients. Eighty-four percent filled at least 1 opioid prescription on discharge. At 30 days following discharge, 8% continued opioid use; at 3 months, 1% continued use; and at 6 months, 0.1%. In the adjusted analysis, the low-intensity surgical procedures were associated with a higher likelihood of discontinuing opioid use (discectomy: hazard ratio [HR] = 1.43, 95% confidence interval [CI] = 1.36 to 1.50; and decompression: HR = 1.34, 95% CI = 1.25 to 1.43). Depression (HR = 0.84, 95% CI = 0.77 to 0.90) was significantly associated with a decreased likelihood of discontinuing opioid use (p < 0.001). Conclusions: By 6 months following discharge, nearly all patients had discontinued opioid use after spine surgery. As only 0.1% of the patients continued opioid use at 6 months following surgery, these results indicate that spine surgery among opioid-naive patients is not a major driver of long-term prescription opioid use. Socioeconomic status and pre-existing mental health disorders may be factors associated with sustained opioid use following spine surgery. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.